Treatment and prevention of Salomellosis in puppies using Lactobacillus acidophilus: Al-Samarrae, S.A.G.; Al-Judi, A.M.H.; Muhsen. R.K. - Al-Samarrae, S. A.G. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was carried out to evaluate the ability of Lactobacillusacidophilus to prevent and treat Salmonella typhimurium in puppies. In vitroantibiotic sensitivity test of S. typhimurium was made and the result revealedthat Ciprofloxacin is the most effective.Isolation of L. acidophilus from theintestinal tract of the normal dogs and also revealed that all Lactobacillus strainswere biochemically identical to standard strain. A bacterial strain that had highability to inhibit the growth of S. typhimurium in vitro with high ability toadhere to intestinal epithelial cells and tolerate the low pH and bile salts waschosen for the experimental study.Twenty puppies were divided into four groups and treated in different ways.The clinical, haematological and biochemical parameters were obtained from allanimals at the period of two days before inoculation until the death of animals ofthe first group at the sixth day post infection. The results revealed that , puppiesexperimentally infected with S.typhimurium showed both septicemic andgastrointestinal forms of the disease accompanied with isolation ofS.typhimurium from the blood and stool throughout the experiment. Thestatistical analysis of the results of all parameters among all groups revealed ,forthe first time, that L.acidophilus plays an important role in the prevention ofS.typhimurium infection in puppies . It also has high therapeutic effect againstS.typhimurium, which was almost similar to that of Ciprofloxacin.